If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 9 + -4(x + 1) = 3x + 9 Reorder the terms: 2x + 9 + -4(1 + x) = 3x + 9 2x + 9 + (1 * -4 + x * -4) = 3x + 9 2x + 9 + (-4 + -4x) = 3x + 9 Reorder the terms: 9 + -4 + 2x + -4x = 3x + 9 Combine like terms: 9 + -4 = 5 5 + 2x + -4x = 3x + 9 Combine like terms: 2x + -4x = -2x 5 + -2x = 3x + 9 Reorder the terms: 5 + -2x = 9 + 3x Solving 5 + -2x = 9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + -2x + -3x = 9 + 3x + -3x Combine like terms: -2x + -3x = -5x 5 + -5x = 9 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + -5x = 9 + 0 5 + -5x = 9 Add '-5' to each side of the equation. 5 + -5 + -5x = 9 + -5 Combine like terms: 5 + -5 = 0 0 + -5x = 9 + -5 -5x = 9 + -5 Combine like terms: 9 + -5 = 4 -5x = 4 Divide each side by '-5'. x = -0.8 Simplifying x = -0.8
| 9x-2=7x+38 | | 0.3(p+6)-0.8(p+6)=-5 | | 3cos(pi)x= | | 16x(x-2)=(8x-25) | | 0.4x-5=.75x-4 | | 0=6x^4-x^3-7x^2+9x+2 | | 16x-9x=840 | | 10t+5(1.4-t)=8 | | -4x+29= | | 7a+7=14 | | 11x+8x=1862 | | 5x(4x+1)(3x-7)=0 | | 2x+9-4x-4(x+1)=3x+9 | | 12(x+2)=24 | | 5x+2=26-3x | | 4(x-1)=x+6 | | v-(-9)=15 | | m+0.72=1.54 | | 5(n-8)(4n+5)=0 | | 53x-x^2=196 | | X+(x+25)+(x-10)=395 | | 2x-7*0=4 | | 2(6x)+19y=310 | | 25x=35 | | 17=6g-13 | | 4000*x^3=5000 | | 81-2x=9-10x | | 12=3g+3 | | 2x+8=-28-4x | | Z=x-a | | (b-7)(b-10)=0 | | 21=27y |